Monitoring Brain Waves during Dhikr: The Foundation for Developing an Islamic Neurofeedback-Based Independent Learning Model - Khundhori Muhammad (Civiliza Publishing, Indonesia., 2025)
This study explores the integration of dhikr spiritual practices with neurofeedback technology to improve self-regulated learning (SRL) skills in Muslim students. Using a mixed method approach, the study involved 30 Muslim students (aged 18-25 years) who underwent a dhikr intervention with neurofeedback for 4 weeks. Brain activity was measured using a 14-channel EEG device, while SRL ability was measured by the Motivated Strategies for Learning Questionnaire (MSLQ) through pre-test, post-test, and follow-up. The results of EEG analysis showed a significant increase in alpha (8-13 Hz) and theta (4-8 Hz) waves, as well as a decrease in beta (13-30 Hz) and gamma (>30 Hz) waves during and after the practice of dhikr. MSLQ measurements showed significant improvements in almost all components of SRL, especially metacognitive ability (d=1.07), self-efficacy (d=0.84), and business regulation (d=0.82). Correlation analysis revealed a strong positive association between increased alpha and theta waves and increased SRL scores. Thematic analysis of semi-structured interviews identified five main themes: increased internal awareness, mental calmness, strengthening of spiritual connections, transfer to learning activities, and the facilitative role of neurofeedback visualization. These findings suggest that the integration of dhikr with neurofeedback has the potential to be an innovative approach to developing SRL abilities while strengthening the religious identity of Muslim students, offering an educational model that integrates cognitive and spiritual aspects.